Renewal of Islamic Family Law: Analysis of The Contribution of Qosim Amin's Thought - Hizbullah, Muhammad; Muhardinata, Imam; Nasution, Leni Masnidar (Al-Fikru: Jurnal Ilmiah, 2023)
Qasim Amin's thoughts have influenced the Islamic family law reform movement in various countries. Although it has faced controversy and criticism, its contribution to positive changes in family law views and practices cannot be overlooked. He has provided the basis for contemporary thinking on how to harmonize Islamic teachings with the values ​​of equality and justice in the context of family law. This study uses a library research approach by searching various sources of literature, especially the works of Qosim Amin, then analyzing them through content analysis methods. The results of this analysis form the basis for drawing conclusions which are then presented in a report. The purpose of this paper is to find out the description and contribution of Qosim Amin in influencing family law in Islam. The results of the study explain that, Qasim Amin's thoughts in reforming Islamic family law include his views on gender equality, wiser polygamy arrangements, and a more equitable distribution of inheritance which have formed the basis for debate and reform of family law that is more modern and in accordance with the values ​​of equality. and justice in contemporary society.